The role of the Ministry of Labor and Social Development initiatives in increasing the participation of Saudi women in the labor market - A field study in Onaiza - Al-Qassim Governorate - - Abdoon, Raga Idress (Journal of Humanities & Social Sciences, 2021)
This study aimed at identifying the extent of women’s self-awareness in the region and their benefits from the initiatives of the Ministry of Labor and Social Development to increase women’s participation in the Saudi labor market. The study included a sample of 96 women of different age groups. The study included ten initiatives, some of them are specific to women and some of them are general ones. The study concluded a number of results and the most important of which is that there is a decline in the knowledge of these initiatives among the sample individuals, as the percentage of knowledge decreased to less than 50% in more than half of these initiatives, whereas there is a very sharp decrease in the percentage of women who benefited from these initiatives as it did not exceed 20% for most of these initiatives, with the exception of the Doroob initiative, where the benefit from it reached 40%. The percentage of evaluating these initiatives as important and of medium importance is more than 90% for all the initiatives. Using the Chi-Square Tests, it was found that there is no statistically significant relationship between knowledge of the initiatives and the variables of age and educational level, with the exception of the initiative of developing productive projects for socially covered families and the initiative to encourage part-time work. As for benefits, there is no statistically significant relationship between benefiting from initiatives and age, with the exception of only two initiatives, and there is also no statistically significant relationship between benefiting from initiatives and the educational level. More than 60% of the sample individuals work in the government sector and 30.4% in the private sector. The percentage of investment in private businesses has decreased to 8%, and more than 60% of non-working women would prefer if they find a job opportunity to work in the government sector, while 37% of them prefer to have their own projects and do not prefer to work in the private sector. The study recommended that more efforts should be made in spreading awareness of initiatives and activating their benefits so as to contribute to their required role in increasing women’s participation in the Saudi labor market.